Norwegian general practitioners' and radiologists' perspectives on the referral, justification, and unnecessary imaging-a survey - Elin Kjelle; Eivind Richter Andersen; Ingrid Øfsti Brandsæter; Bjørn Morten Hofmann (Taylor & Francis Group, 2024)
Aim This study aimed to survey general practitioners' (GPs) and radiologists' perspectives on referrals, imaging justification, and unnecessary imaging in Norway.Materials and methods The survey covered access to imaging, responsibilities, attitudes toward justification assessment, referral process, and demographics using multiple choice questions, statements to report agreement with using the Likert scale and one open question.Results Forty radiologists and 58 GPs attending national conferences completed a web-based survey, with a 20/15% response rate, respectively. Both radiologists (97%) and GPs (100%) considered avoiding unnecessary examinations essential to their role in the healthcare service. Still, 91% of GPs admitted that they referred to imaging they thought was not helpful, while about 60% of the radiologists agreed that unnecessary imaging was conducted in their workplace. GPs reported pressure from patients and patients having private insurance as the most common reasons for doing unnecessary examinations. In contrast, radiologists reported a lack of clinical information and the inability to discuss patient cases with the GPs as the most common reasons.Conclusion This study adds to our understanding of radiologists' and GPs' perspectives on unnecessary imaging and referrals. Better guidelines and, even more importantly, better communication between the referrer and the radiologist are needed. Addressing these issues can reduce unnecessary imaging and improve the quality and safety of care.